Enhancing interdisciplinary climate change work through comprehensive evaluation - Jenna Klink; Vikram Koundinya; Kim Kies; Courtney Robinson; Amulya Rao; Claire Berezowitz; Melissa Widhalm; Linda Prokopy (Climate Risk Management, 2017)
This paper shares the details of an evaluation plan from an interdisciplinary climate change project that developed decision support tools (DSTs) for agricultural advisors and farmers. It showcases how evaluation enhanced the project work by providing opportunities for the team to reflect on and use data to improve performance. The plan included both formative and summative approaches, team member interviews to assess team functioning, usability testing of DSTs, outreach and marketing campaign evaluation. Outreach evaluation included surveying those reached, monitoring project website traffic, and tracking and mapping outreach details. Marketing evaluation included pre-testing campaign materials, assessing open and click rates of email campaign, and monitoring associated traffic to website. The Useful to Usable (U2U) team was generally high functioning, but team interviews allowed the evaluators and leaders to discern factors that were influencing intended outcomes, respond to needs, assign resources, and catalyze activities that were crucial in shaping the outcomes. Usability testing surfaced issues related to default values and search and help features that were addressed by the team and resulted in improved usability. Outreach evaluation found geographic and methodological gaps that were filled, resulting in more target audiences reached and more effective methods used (e.g., hands-on events). Marketing evaluation allowed for improving contact lists over time and improving campaign messaging before deployment. Evaluators and project leaders working on similar projects may adapt or utilize methods detailed in this paper, along with the recommendations, while designing and implementing improvement-oriented evaluation plans.